Implementasi Lean Manufacturing di PT. Gerem Jaya - Kurniaty Ratoko, Sita; Irpan Sabila, Ade (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
Gerem is a household furniture company specializing in the production of home door leaves and wooden home accessories. Currently, the issues faced by PT. Gerem include irregular orders, product variations leading to overproduction, resulting in the risk of excess stock, which can cause product damage due to prolonged storage and wastage of time if they need to be reworked. This issue primarily occurs in the production of door leaves. Identification through interviews and observations reveals wastage, including scrap, rejected products, extended processes due to machine failures, and rework due to measurement errors and defective products. In an effort to improve productivity, the company utilizes a lean approach to identify and eliminate waste using Value Stream Analysis Tools (VALSAT). This research has found that the longest time is spent on the measurement, cutting, and wood planing processes, with a lead time of 120 minutes. The analysis of waste calculations uses the Waste Relationship Matrix (WRM) and identifies defects as the biggest source of waste (20.56% vertical and 19.63% horizontal). Based on this, improvement planning is carried out with the design of a future state mapping, reducing the operation time to 170 minutes, reducing the storage of finished products to about 2 days, and achieving a delay of 0 minutes. This increases productivity by organizing the number of employees in each production process